Model Pembelajaran Creative Problem Solving (CPS) Untuk Mengembangkan Kemampuan Berpikir Kreatif Matematis Siswa - Ridho Saputra, Muhammad; Yulia; Fajriah, Wina (Lattice Journal : Journal of Mathematics Education and Applied, 2024)
The creative mathematical thinking abilities of 9th-grade students at SMP N 1 2x11 Enam Lingkung are lacking. This is evident in their difficulty generating multiple ideas and struggling to find solutions when tackling exercise questions. Introducing the Creative Problem Solving (CPS) learning model is proposed as a potential solution to this issue. This study aims to compare the mathematical creative thinking skills of 9th-grade students at SMP N 1 2x11 Enam Lingkung who are exposed to the CPS learning model. Using a Quasi-Experimental design, specifically a Randomized Control Group Only Design, the study selects class IX.A as the experimental group and class IX.E as the control group. The results of this study obtained the average score of mathematical creative thinking ability in the experimental class (CPS) which was 78.125, while in the control class with scientific learning, it was 68.125. From the data processing of students' mathematical creative thinking skills, it was carried out through a t-test, so that, .= 6.3192 while in df = 62 with a confidence level of 95%   was obtained. 1.99. Because of, . 6.3192 >  . 1.99. Therefore, it is concluded that the mathematical creative thinking ability of students by applying the CPS type cooperative learning model is higher than the mathematical creative thinking ability of students with scientific learning   Kemampuan berpikir kreatif matematis siswa kelas IX SMP N 1 2x11 Enam Lingkung belum berkembang dengan baik. Hal ini ditunjukkan saat siswa menjawab soal latihan yang diberikan siswa belum mampu menghasilkan banyak ide dan tidak lancar dalam menemukan solusi. Menerapkan model pembelajaran Creative Problem Solving (CPS) menjadi salah satu cara untuk mengatasi permasalahan tersebut. Penelitian ini bertujuan untuk membandingkan kemampuan berpikir kreatif matematis siswa kelas IX di SMP N 1 2x11 Enam Lingkung yang belajar menggunakan model pembelajaran CPS. Jenis penelitian ini adalah True Experiment, dan desain Randomized Control Grup Only Design. Populasi penelitian ini adalah siswa kelas IX dan sampel terpilih kelas IX.A untuk eksperimen dan kelas IX.E untuk kontrol.  Hasil penelitian ini mendapatkan nilai rata-rata kemampuan berpikir kreatif matematis kelas eksperimen (CPS) yaitu 78,125, sedangkan pada kelas kontrol dengan pembelajaran saintifik yaitu 68,125. Dari pengolahan data kemampuan berpikir kreatif matematis siswa dilakukan melalui uji-t, sehingga diperoleh = 6,3192 sedangkan pada df = 62 dengan taraf kepercayaan 95% diperoleh  1,99. Karena  6,3192 >  1,99. sehingga disimpulkan kemampuan berpikir kreatif matematis siswa dengan menerapkan model pembelajaran kooperatif tipe CPS lebih tinggi daripada kemampuan berpikir kreatif matematis siswa dengan pembelajaran saintifik